Nanomaterial marvels: Pioneering applications and cutting-edge advancements in drug delivery - Chatterjee, Priyajit; Dhibar, Subhendu (Nano and Medical Materials, 2023)
Nanotechnology has revolutionized the field of medicine, particularly in the development of novel drug delivery systems. Nanomaterial-based drug delivery systems offer several advantages over traditional methods, including enhanced therapeutic efficacy, improved bioavailability, targeted delivery, and reduced side effects. This review provides an overview of the applications and recent advancements in nanomaterial-based drug delivery systems. The first section of this review focuses on the different types of nanomaterials used in drug delivery, including liposomes, polymeric nanoparticles, dendrimers, carbon-based nanomaterials, and metallic nanoparticles. Each nanomaterial has unique physicochemical properties that can be tailored to optimize drug encapsulation, release, and targeting. The second section highlights the importance of nanoscale characterization techniques in evaluating the properties and performance of nanomaterial-based drug delivery systems. Characterization techniques such as dynamic light scattering, transmission electron microscopy, atomic force microscopy, and spectroscopic methods enable researchers to analyze particle size, morphology, surface charge, drug loading, and release kinetics. The third section discusses the application of nanomaterial-based drug delivery systems in various therapeutic areas, including cancer treatment, cardiovascular diseases, infectious diseases, and neurological disorders. These systems can be engineered to selectively accumulate at the target site, enhancing drug efficacy and minimizing off-target effects. The fourth section explores recent advancements in nanomaterial-based drug delivery systems, including stimulus-responsive and multifunctional nanocarriers. Stimuli-responsive systems can release drugs in response to specific triggers, such as changes in pH, temperature, or enzymatic activity, leading to site-specific drug release. Multifunctional nanocarriers combine drug delivery with diagnostic imaging, allowing real-time monitoring of drug distribution and therapeutic response. The final section addresses the challenges and future perspectives in the field of nanomaterial-based drug delivery systems. Challenges include regulatory considerations, toxicity concerns, scalability, and clinical translation. Future directions involve the development of personalized nanomedicine, combination therapy approaches, and integration with other emerging technologies, such as artificial intelligence and gene editing. In conclusion, nanomaterial-based drug delivery systems have shown great potential for improving the efficacy and safety of therapeutic interventions. The advancements in nanotechnology offer exciting opportunities for the development of next-generation drug delivery platforms, opening new avenues for personalized medicine and targeted therapies. However, further research and collaborations are required to address the challenges associated with clinical translation and ensure the safe and effective implementation of these systems in clinical practice.